PELAKSANAAN GOOD GOVERNANCE PADA INSTANSI PEMERINTAH - Mega Erita (Universitas Riau, 2016)
Implementation of Good Governance in Government Agencies. This study of how theactual implementation of good governance, especially at the Office of National Unity, Politics andPublic Protection (Kesbangpolinmas) year from 2012 to 2014 in the city of Dumai. Based onresearch conducted Kesbangpolinmas Office of Dumai yet implementing or applying the valuesof good governance in committed, especially against the three main principles, namely, theimplementation of principles of participation, transparency and accountability. The method usedis a qualitative research method in which one of the research procedures that produce descriptivedata and the data obtained more complete, more deeply so that the research objectives can beachieved. The research location is on the Office of National Unity, Politics and Public ProtectionDumai. Authors gather research data from several books, government regulations, journals andinterviews with informants research that Kesbangpolinmas office clerks, community organizationsand political parties. This research resulted in the conclusion that the obstacles in theimplementation of good governance at the Office of National Unity, Politics and Public Protectionin 2012-2014 in Kota Dumai is intenal factors which include officials from the institutions andattitudes. As well as from external factors include CSOs / NGOs and political parties. Therefore, theOffice Kesbangpolinmas more attention to performance, whether it is in accordance with applicableregulations. To avoid obstacles in conducting a policy especially related to society.